Reduction of platinum (IV) ions to elemental platinum nanoparticles by anaerobic sludge - Simon-Pascual, Alvaro (J Chem Technol Biotechnol, 2017)
BACKGROUND: The future supply of platinum group metals (PGM) is at risk because of their scarcity combined with a high demand. Thus recovery of platinum (Pt) from waste is an option worthy of study to help alleviate future shortages. This research explored the microbial reduction of platinum (Pt). The ability of anaerobic granular sludge to reduce Pt(IV) ions under different physiological conditions was studied. RESULTS: X-Ray diffraction (XRD) and transmission electron microscope (TEM) analyses demonstrated the capacity of the microbial mixed culture to reduce Pt(IV) to Pt(0) nanoparticles, which were deposited on the cell-surface and in the periplasmic space. Ethanol supported the biologically catalyzed Pt(IV) reduction, meanwhile other electron donors; hydrogen (H(2)) and formate, promoted the chemical reduction of Pt(IV) with some additional biological stimulation in the case of H(2). A hypothesis is proposed in which H(2) formed from the acetogenesis of ethanol is implicated in subsequent abiotic reduction of Pt(IV) indicating an integrated bio-chemical process. Endogenous controls also resulted in slow Pt(IV) removal from aqueous solution. Selected redox mediators, exemplified by riboflavin, enhanced the Pt(IV) reduction rate. CONCLUSION: This study reported for the first time the ability of an anaerobic granular sludge to reduce Pt(IV) to elemental Pt(0) nanoparticles.